2022
DOI: 10.31965/infokes.vol20.iss1.627
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Black Cumin (Nigella Sativa) on Breastfeeding Mothers

Abstract: Breast milk is the best nutrient to reduce the pain in nursing mothers and death in infants. However, for nursing mothers, too little milk volume is the cause of problems occurring during the breastfeeding process. Thus, mothers who breastfeed should consume foods that can increase the breast milk volume. One food frequently consumed by mothers to increase breast milk is honey. In fact, natural honey is challenging to discover, and the price is also high which makes it as an obstacle. A more economical alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In line with this opinion, a previous study found that there was an effect of women's knowledge after video viewing on the implementation of early initiation of breastfeeding with a statistically significant p-value of 0.006<0.05 (Apriastuti, 2016). Several studies revealed that health education about the benefits of breastfeeding through breastfeeding technique during pregnancy was an important factor in increasing the implementation of early initiation of breastfeeding after childbirth (Hawkins, et al, 2015;Jiang et al, 2015;Sihombing et al, 2022;Zakaria & Astuti, 2022).…”
Section: Resultsmentioning
confidence: 76%
“…In line with this opinion, a previous study found that there was an effect of women's knowledge after video viewing on the implementation of early initiation of breastfeeding with a statistically significant p-value of 0.006<0.05 (Apriastuti, 2016). Several studies revealed that health education about the benefits of breastfeeding through breastfeeding technique during pregnancy was an important factor in increasing the implementation of early initiation of breastfeeding after childbirth (Hawkins, et al, 2015;Jiang et al, 2015;Sihombing et al, 2022;Zakaria & Astuti, 2022).…”
Section: Resultsmentioning
confidence: 76%
“…Providing additional recovery food (PMT-P), whose nutritional value has been measured so that nutritional needs can be met, is one method to combat malnutrition. There is an effect of supplemental feeding on the growth of children under the red line, indicating that the growth of children under the red line influences the supplementary feeding intervention (Zakaria & Astuti, 2022).…”
Section: Resultsmentioning
confidence: 99%